Comparative Analysis for Loss Control in Power Transmission System via Composite Compensation Scheme - Ismail S.A.; Musirin I.; Mansor M.H.; Hamid Z.A.; Senthil Kumar A.V.; Abdullah A.; Jelani S. (Institute of Electrical and Electronics Engineers Inc., 2025)
Loss minimization in power system is still relevant in power system community. Its presence may lead to overcompensation or under-compensation if no proper compensation strategy is properly planned, especially a reliable optimization technique. One important initiative to alleviate the transmission burden which meets the load demand can be rectified by composite compensation scheme. This paper proposed a composite compensation which integrates the multiunit of distributed generation (DG) and optimal reactive power dispatch (ORPD) which identifies the amount of reactive power to be dispatched by the generators in the system. In this study, a new and fast mutation technique is introduced to the original evolutionary programming (EP) optimization technique. It is termed Integrated Cloning Accelerated Mutation Evolutionary Programming (ICAMEP). ICAMEP was introduced to alleviate the weakness in the standalone EP and AIS which normally stuck as local optima. The study identifies optimal locations and sizes for composite compensation in the power transmission system, demonstrating its superiority over traditional EP and artificial immune systems (AIS). The impact of multi DGs installation, validated on IEEE 30-Bus Reliability Test System (RTS) was analyzed which can help the relevant utility to make future plan and decision. ? 2024 IEEE.